KEPRAKTISAN MEDIA PARASIS PEPAMA DALAM MENINGKATKAN HASIL BELAJAR IPAS SISTEM PERNAPASAN DI SEKOLAH DASAR - Najwa Durrotul Hikmah; Fera Dwidarti; Badri Atul Fikriyah3 (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to measure the practicality of the parasis pepama media in improving IPAS learning outcomes in the respiratory system at school. Learning at the primary school level plays an important role in shaping students' scientific thinking. One of the materials that poses a particular challenge because it contains abstract concepts that cannot be directly observed by students is the respiratory system. Therefore, appropriate learning media are needed to overcome this challenge. This study employs a quantitative descriptive approach with data collection techniques through a practicality questionnaire administered to teachers and students. The practicality test results indicate that the instrument was rated as highly practical by teachers at 91% and by students at 87%, with an overall average of 90.5%. These findings indicate that the Parasis Pepama media in improving IPAS learning outcomes on the respiratory system is easy to use, efficient in implementation, and attractive and adaptive for users in the elementary school environment. In conclusion, the Parasis Pepama media has a very good level of practicality and can be an alternative learning medium. This media has the potential to support student engagement and facilitate teachers in managing classroom learning.